2022
DOI: 10.1039/d2dt00876a
|View full text |Cite
|
Sign up to set email alerts
|

Differences in chemoselectivity in olefin oxidation by a series of non-porphyrin manganese(iv)-oxo complexes

Abstract: High valent metal-oxo intermediates are versatile oxidants known to facilitate both oxygen atom transfer (OAT) and hydrogen atom transfer (HAT) reactions in nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 79 publications
(59 reference statements)
0
18
0
Order By: Relevance
“…Thermodynamic Contributions to Reactivity for Mn IV -Oxo Complexes. We have previously observed correlations between thermodynamic parameters and the reactivity of Mn IV -oxo complexes, 28 and the new data reported here for [Mn IV (O)(N3pyQ)] 2+ and [Mn IV (O)(N4py Me2 )] 2+ allow us to evaluate the robustness of these correlations. We still observe an excellent linear correlation between the rates of thioanisole oxidation (as log(k 2 )) and the DFT-calculated Mn IV �O BDFE when considering the new complexes (Figure 12, top, and Table S9).…”
Section: ■ Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Thermodynamic Contributions to Reactivity for Mn IV -Oxo Complexes. We have previously observed correlations between thermodynamic parameters and the reactivity of Mn IV -oxo complexes, 28 and the new data reported here for [Mn IV (O)(N3pyQ)] 2+ and [Mn IV (O)(N4py Me2 )] 2+ allow us to evaluate the robustness of these correlations. We still observe an excellent linear correlation between the rates of thioanisole oxidation (as log(k 2 )) and the DFT-calculated Mn IV �O BDFE when considering the new complexes (Figure 12, top, and Table S9).…”
Section: ■ Discussionmentioning
confidence: 98%
“…15 While the multistate reactivity model has been extremely useful in developing and understanding the reactivity of Mn IVoxo complexes, in a recent study, we showed that the trend in C−H bond oxidation rates for these complexes can also be understood in terms of thermodynamic properties. 28 Specifically, the log k 2 for 9,10-dihydroanthracene (DHA) oxidation showed a linear correlation with the strength of the O−H bond in the Mn III -hydroxo products (Figure 1, right). A correlation was also found between oxygen-atom transfer rates and the Mn�O bond strength of Mn IV -oxo complexes.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The selective oxidation of the C-H bond is one of the most common processes to produce high-value-added chemicals, such as hydroperoxides, alcohols, ketones, aldehydes, carboxylic acids and epoxides. [1][2][3][4][5] For example, acetophenone is an important raw material for the production of drugs, spices, resins, flavoring agents and many other drugs, and can be produced through the oxidation of ethylbenzene. 6 However, industrial acetophenone is mainly synthesized by the decomposition of cumene hydroperoxide or Friedel-Crafts acylation reaction.…”
Section: Introductionmentioning
confidence: 99%